2019
DOI: 10.1111/lang.12367
|View full text |Cite
|
Sign up to set email alerts
|

Different Perspectives on Critical Factors in Heritage Language Development and Maintenance

Abstract: Heritage languages (HLs) are acquired in contexts of unbalanced input, or situations in which children receive primary exposure to the family/HL and experience an abrupt shift after the child begins formal schooling. As a consequence, HL speakers normally become more dominant in the environmental language, while the development of the HL is characterized by variable outputs. This means that HL speakers display more variation in their acquisition process and their “final state” competence compared to speakers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Moreover, there has been much discussion in recent literature in the field of bilingualism about the need to consider the multidimensionality of bilingualism in order to better understand the cognitive consequences of bilingualism (e.g., Abutalebi & Green, ; Bialystok, ; Green & Abutalebi, ; Kroll & Bialystok, ; Laine & Lehtonen, ; Luk & Bialystok, ; Surrain & Luk, ; Takahesu Tabori, Mech, & Atagi, ). For instance, there have been calls to treat bilingualism as a continuous variable (e.g., Luk & Bialystok, ), to examine the contexts of bilinguals’ language use (e.g., Abutalebi & Green, ; Green & Abutalebi, ), and more generally, to consider the diversity in language experience that exists among bilinguals (e.g., Flores, Gürel, & Putnam, ; Ortega, ; Takahesu Tabori et al., ). Similarly, findings from this study—as well as those from others (e.g., Akhtar et al., ; Howard et al., ; Menjivar & Akhtar, ; Rojo & Echols, )—suggest that monolinguals may not be a homogenous group either, much like bilinguals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there has been much discussion in recent literature in the field of bilingualism about the need to consider the multidimensionality of bilingualism in order to better understand the cognitive consequences of bilingualism (e.g., Abutalebi & Green, ; Bialystok, ; Green & Abutalebi, ; Kroll & Bialystok, ; Laine & Lehtonen, ; Luk & Bialystok, ; Surrain & Luk, ; Takahesu Tabori, Mech, & Atagi, ). For instance, there have been calls to treat bilingualism as a continuous variable (e.g., Luk & Bialystok, ), to examine the contexts of bilinguals’ language use (e.g., Abutalebi & Green, ; Green & Abutalebi, ), and more generally, to consider the diversity in language experience that exists among bilinguals (e.g., Flores, Gürel, & Putnam, ; Ortega, ; Takahesu Tabori et al., ). Similarly, findings from this study—as well as those from others (e.g., Akhtar et al., ; Howard et al., ; Menjivar & Akhtar, ; Rojo & Echols, )—suggest that monolinguals may not be a homogenous group either, much like bilinguals.…”
Section: Discussionmentioning
confidence: 99%
“…This methodological innovation—which, to our knowledge, has no precedent in the vast literature on HSs and mood—both controls the characteristics of the targeted verbs, making them maximally comparable, and opens up the possibility of uncovering previously unidentified patterns of intraspeaker mood variability, for example, that some HSs reliably differentiate between subjunctive and indicative forms but only with certain subsets of their Spanish language lexicon. In identifying, by means of a within‐verbs methodology, the way that HSs’ production of mood varies with different lexical items, we sidestep debates about labeling HL grammars (e.g., as “incomplete” or “divergent”) and instead focus our attention on “elucidating why HSs acquire what they do by considering how the interaction of a myriad of cognitive, linguistic and social factors shape heritage speakers [sic] unique linguistic knowledge” (López‐Beltrán & Carlson, 2020, p. 5; and see Flores, Gürel, & Putnam, 2020, for related arguments). The promise of this approach will be evident, we believe, in both the new patterns that it uncovers and, more importantly, the new questions that it inspires.…”
Section: Discussionmentioning
confidence: 99%
“…The critical factors of HL learning and development often include age of immigration or age of onset of bilingualism, parental education, SES, and birth order (e.g., Ahn et al, 2017;Armon-Lotem et al, 2015;Kim & Pyun, 2015;Montrul, 2008), parents' attitudes and home environment (e.g., Kang, 2015;Park & Sarkar, 2007), community engagement (e.g., Leeman et al, 2011), ethnic and cultural identity (e.g., Lee, 2002), school ideologies and teachers' attitudes (e.g., Seals, 2018;Yilmaz, 2016), and societal accessibility to HL learning (e.g., Becker, 2013). However, debates on the critical factors are ongoing due to the varying contexts, dynamics among factors, and methodological issues (Duff, 2019;Flores et al, 2020;Ortega, 2020).…”
Section: Hl Learning and Various Factorsmentioning
confidence: 99%
“…Scholarship has investigated various individual, academic, familial, social, and national benefits of HL development and maintenance, stressing the importance of HL maintenance (e.g., Guardado, 2010;Guardado & Becker, 2014;Kang, 2013;Lee & Suarez, 2009;Park, 2013;Tse, 2000;Wong Fillmore, 1991). Studies have also revealed numerous linguistic, individual, familial, and sociocultural factors which facilitate and hinder HL learning and development, through various approaches such as sociolinguistic perspectives and usage-based approaches (see Flores et al, 2020;Lynch, 2014). Language development largely relies on the amount and quality of "exposure to relevant language input" (Ortega, 2020, p. 27), but HL learners are exposed to unbalanced input while becoming dominant in the main language in society.…”
mentioning
confidence: 99%